Critical realism : essential readings - Archer, Margaret S. (Margaret Scotford); Bhaskar, Roy, 1944-2014; Collier, Andrew, 1944-2014; Lawson, Tony, 1950-; Norrie, Alan W. (Alan William), 1953- (Routledge, 2013)
Critical realism is a movement in philosophy and the human sciences most closely associated with the work of Roy Bhaskar. Since the publication of Bhaskar's 'A Realist Theory of Science', critical realism has had a profound influence on a wide range of subjects. This reader makes accessible, in one volume, key readings to stimulate debate about and within critical realism. It explores the following themes: * transcendental realist * the theory of explanatory critique * dialectics * Bhaskar's critical naturalist philosophy of science.